2017
DOI: 10.2209/tdcpublication.2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Radiographic Success of Electrosurgical Pulpectomy in Primary Teeth

Abstract: A pulpectomy requires the swift extraction of the inflamed tissue. Moreover, the speed of treatment is especially important in the case of uncooperative children. Conventional pulpectomies, however, often require an extended treatment period, which can therefore cause problems with such patients. Electrosurgical methods have been applied to pulpotomies for a number of years. However, to the best of our knowledge, no studies to date have assessed its application to pulpectomies. The aim of this study was to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1 It is worth mentioning that the clinical and radiographic frequencies of success should be carefully analysed and compared, since there is no consensus regarding an ideal standard protocol for the pulpectomy procedure. 2 While most of the studies reported a single intervention visit, 5,6,[9][10][11][12][13][17][18][19]21,22,24,26,32,33 other studies twovisits 9,15,16,23,28,29,31,34 and two did not present the information 20,30 . In addition, regarding the filling techniques, the use of lentulo spirals, 5,6,10-13,15,17,22-24,29,32,34 syringes 6,9,10,16,18,19,21,29,32,33 and K-file 32 were reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is worth mentioning that the clinical and radiographic frequencies of success should be carefully analysed and compared, since there is no consensus regarding an ideal standard protocol for the pulpectomy procedure. 2 While most of the studies reported a single intervention visit, 5,6,[9][10][11][12][13][17][18][19]21,22,24,26,32,33 other studies twovisits 9,15,16,23,28,29,31,34 and two did not present the information 20,30 . In addition, regarding the filling techniques, the use of lentulo spirals, 5,6,10-13,15,17,22-24,29,32,34 syringes 6,9,10,16,18,19,21,29,32,33 and K-file 32 were reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is also indicated in case of primary molars or incisors caries that necessitates application of a maintenance arch. 25,26 Pulpectomy can also be used in cases of primary dentitions with necrotic pulps and pulp less primary dentitions particularly when a space maintainer is indicated. 9,11 However, it is not suitable for teeth with underlying cystic lesions (e.g.…”
Section: Pulpectomy Techniques Indications Complicationsmentioning
confidence: 99%